2020
DOI: 10.1186/s13287-020-01992-1
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle healing by M1-like macrophages produced by transient expression of exogenous GM-CSF

Abstract: Background After traumatic skeletal muscle injury, muscle healing is often incomplete and produces extensive fibrosis. The sequence of M1 and M2 macrophage accumulation and the duration of each subtype in the injured area may help to direct the relative extent of fibrogenesis and myogenesis during healing. We hypothesized that increasing the number of M1 macrophages early after traumatic muscle injury would produce more cellular and molecular substrates for myogenesis and fewer substrates for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 66 publications
2
24
0
Order By: Relevance
“…Macrophages can be classified as M1, which are present during the inflammatory stage of skeletal muscle regeneration, or M2, which accumulate at the site of injury once necrotic tissue has been removed and participate in the regeneration and remodelling response (Martins et al., 2020). There were differential responses in our markers of macrophage polarization at the 8‐week time point.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages can be classified as M1, which are present during the inflammatory stage of skeletal muscle regeneration, or M2, which accumulate at the site of injury once necrotic tissue has been removed and participate in the regeneration and remodelling response (Martins et al., 2020). There were differential responses in our markers of macrophage polarization at the 8‐week time point.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a dramatic increase in the number of CD45 + hematopoietic cells on ischemia day 2 (Supplementary Figure 5 c). Inflammatory regulation is known to be tightly associated with muscle regeneration [ 32 , 56 ] and angiogenesis [ 32 , 34 ], and pericytes are known to exhibit an immunomodulatory ability [ 19 , 20 , 50 , 51 ]. Notably, pericytes upregulated the expression of signaling molecules that attract inflammatory cells ( Ccl2, Ccl3, Ccl4 , and Cxcl5 ) and molecules that stimulate inflammation ( Il1b and Tnf ) at the earliest time point (ischemic day 2) (Supplementary Figure 5 a).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in our laboratory [ 30 34 ] and by other researchers [ 35 , 36 ] have shown that monocytes, macrophages, and MSCs have the potential to regulate angiogenesis, myogenesis, and fibrogenesis in skeletal muscle; therefore, the cells and/or genes that modulate these processes may provide insight into limb ischemia treatment. The role of pericytes in the recovery process from limb ischemia, however, has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…5C). In ammatory regulation is known to be tightly associated with muscle regeneration [32,55] and angiogenesis [32,34], and pericytes are known to exhibit an immunomodulatory ability [19,20,50,51]. Notably, pericytes upregulated the expression of signaling molecules that attract in ammatory cells (Ccl2, Ccl3, Ccl4, and Cxcl5) and molecules that stimulate in ammation (Il1b and Tnf) at the earliest time point (ischemic day 2) ( Supplementary Fig.…”
Section: Expression Of Genes Encoding Cytokines In Pericytesmentioning
confidence: 98%
“…Previous studies conducted in our laboratory [30][31][32][33][34] and by other researchers [35,36] have shown that monocytes, macrophages and MSCs have the potential to regulate angiogenesis, myogenesis, and brogenesis in skeletal muscle; therefore, the cells and/or genes that modulate these processes may provide insight into limb ischemia treatment. The role of pericytes in the recovery process from limb ischemia, however, has not been extensively studied.…”
Section: Introductionmentioning
confidence: 95%